The Psychometric Properties of the Norwegian version of Parenting Stress Index (PSI), 2. edition - Wessel, Pål; Kyrrestad, Henriette (PsykTestBarn, 2024)
Description: The Parenting Stress Index (PSI) is an inventory designed to measure parenting stress in the parent-child relationship and is available in a full and short form version. The inventory was developed by Richard R. Abidin in 1995 and translated into Norwegian by John A. Rønning in 2006. The PSI consists of a child domain with six subscales and a parent domain with seven subscales, which together form a total stress score. Additionally, the inventory includes a scale for life stress. The short-form version of the PSI (PSI-SF) consists of three subscales, which together form a total stress score. The questionnaire is intended to be answered by parents with children aged from one month to 12 years. PSI is designed for both research and clinical purposes. Both forms require a license and approval from the copyright holder PAR, Inc. to be used. Literature search: A systematic literature search was conducted for Scandinavian publications reporting measurement properties of the PSI and PSI-SF. Out of 444 identified studies, 26 Norwegian publications were included; four studies used PSI-SF, and 22 used PSI. No Swedish or Danish studies met the inclusion criteria. Psychometrics: Adequate to excellent internal consistency was found on all scales. Most studies reported means and standard deviations for various subgroups, with scores for both PSI and PSI-SF indicating good construct validity. Correlations with other measurement instruments varied from inadequate to good for the PSI. Sensitivity to change suggests that full version of the PSI may be responsive to changes over time. No Scandinavian norms for either PSI or PSI-SF were identified. Conclusion: The Norwegian version of PSI demonstrates good internal consistency and construct validity. The full version of the PSI has been more extensively utilized in recent years compared to the PSI-SF. The psychometric properties of PSI have mainly been documented through studies involving parents of infants and toddlers. Therefore, there is a need to document the psychometric properties of PSI among parents with children aged 9 years to 12 years. Additionally, there is a need to develop Scandinavian norms.